Criminal governance for the protection of public funds in the age of artificial intelligence: A prospective analytical study within the Algerian legal framework - Beroual, Nadjib; Terki, Walid (The International tax journal, 2026)
The management of public funds in Algeria is undergoing profound transformations as a result of the rapid expansion of public administration digitization and the increasing reliance on artificial intelligence technologies in public finance domains, such as public procurement, taxation, and treasury management. While this digital transformation has contributed to enhancing efficiency and promoting transparency, it has simultaneously generated emerging legal risks that threaten the integrity of public funds. This is particularly evident with the rise of new forms of intelligent crimes based on algorithmic manipulation of data, deepfake technologies, and indirect digital embezzlement—practices that often exceed the regulatory and deterrent capacity of traditional criminal law provisions. This study aims to analyze the extent to which the Algerian criminal justice system is capable of establishing effective criminal governance to protect public funds in the face of AI-driven digital risks. It does so by examining the conceptual framework of intelligent crime, analyzing the issue of criminal liability within algorithmic environments, and assessing the effectiveness of the currently adopted preventive and punitive mechanisms. The research adopts an analytical approach in examining relevant national legal texts, alongside a prospective approach to anticipate the future of criminal policy in addressing intelligent crimes.